Out of the Palaeotropics? Historical biogeography and diversification of the cosmopolitan ectomycorrhizal mushroom family Inocybaceae - P. Brandon Matheny; M. Catherine Aime; Neale L. Bougher; Bart Buyck; Dennis E. Desjardin; Egon Horak; Bradley R. Kropp; D. Jean Lodge; Kasem Soytong; James M. Trappe; David S. Hibbett (My University, 2009)
Abstract Aim The ectomycorrhizal (ECM) mushroom family Inocybaceae is widespread in north temperate regions, but more than 150 species are encountered in the tropics and the Southern Hemisphere. The relative roles of recent and ancient biogeographical processes, relationships with plant hosts, and the timing of divergences that have shaped the current geographic distribution of the family are investigated. Location Africa, Australia, Neotropics, New Zealand, north temperate zone, Palaeotropics, Southeast Asia, South America, south temperate zone. Methods We reconstruct a phylogeny of the Inocybaceae with a geological timeline using a relaxed molecular clock. Divergence dates of lineages are estimated statistically to test vicariance‐based hypotheses concerning relatedness of disjunct ECM taxa. A series of internal maximum time constraints is used to evaluate two different calibrations. Ancestral state reconstruction is used to infer ancestral areas and ancestral plant partners of the family. Results The Palaeotropics are unique in containing representatives of all major clades of Inocybaceae. Six of the seven major clades diversified initially during the Cretaceous, with subsequent radiations probably during the early Palaeogene. Vicariance patterns cannot be rejected that involve area relationships for Africa–Australia, Africa–India and southern South America–Australia. Northern and southern South America, Australia and New Zealand are primarily the recipients of immigrant taxa during the Palaeogene or later. Angiosperms were the earliest hosts of Inocybaceae. Transitions to conifers probably occurred no earlier than 65 Ma. Main conclusions The Inocybaceae initially diversified no later than the Cretaceous in Palaeotropical settings, in association with angiosperms. Diversification within major clades of the family accelerated during the Palaeogene in north and south temperate regions, whereas several relictual lineages persisted in the tropics. Both vicariance and dispersal patterns are detected. Species from Neotropical and south temperate regions are largely derived from immigrant ancestors from north temperate or Palaeotropical regions. Transitions to conifer hosts occurred later, probably during the Palaeogene.
Keywords: Vicariance; Disjunct; Disjunct distribution; Paleogene; Mycorrhizal Fungi and Plant Interactions